2006
DOI: 10.1002/star.200500459
|View full text |Cite
|
Sign up to set email alerts
|

Pasting Properties of Non‐waxy Rice Starch‐Hydrocolloid Mixtures

Abstract: The swelling and pasting properties of non-waxy rice starch-hydrocolloid mixtures were investigated using commercial and laboratory-generated hydrocolloids. The swelling power of the rice starch-hydrocolloid mixtures was generally depressed at low concentration of hydrocolloids (0-0.05%), but increased directly with increasing hydrocolloid concentrations (0.05-0.1%). In gellan gum dispersion, the swelling power at 1007C was higher than that of control. The rice starch-hydrocolloids mixtures showed shear-thinni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 73 publications
(39 citation statements)
references
References 20 publications
4
33
1
1
Order By: Relevance
“…On the other hand, CAR addition, starting from 0.25% concentration, slightly affected the pasting viscosities of the cassava starch. Song et al (2006) and Chaisawang and Suphantharika (2006) reported similar results when evaluating the pasting properties of mixtures of rice, and native and cationic cassava starches and different gums, among them, xanthan and guar gums. According to theses authors the higher peak, breakdown, and final viscosities of starch-gum mixtures, in comparison to starchwater, occurred because of the starch-gum system is biphasic with the gum located within the continuous phase.…”
Section: Pasting Propertiesmentioning
confidence: 66%
See 4 more Smart Citations
“…On the other hand, CAR addition, starting from 0.25% concentration, slightly affected the pasting viscosities of the cassava starch. Song et al (2006) and Chaisawang and Suphantharika (2006) reported similar results when evaluating the pasting properties of mixtures of rice, and native and cationic cassava starches and different gums, among them, xanthan and guar gums. According to theses authors the higher peak, breakdown, and final viscosities of starch-gum mixtures, in comparison to starchwater, occurred because of the starch-gum system is biphasic with the gum located within the continuous phase.…”
Section: Pasting Propertiesmentioning
confidence: 66%
“…On the whole, at higher concentrations, this hydrocolloid caused a reduction in the SP of the mixture when compared to the starch-water system. Song et al (2006) observed a reduction in the SP of rice starch when guar, xanthan, and Arabic gums were added to this starch, but they observed an increase in the SP when gellan gum was used. These authors justified this reduction due to the osmotic pressure generated within the continuous phase of the gum resulting from the swelling of the starch phase.…”
Section: Dynamic Rheological Behaviormentioning
confidence: 95%
See 3 more Smart Citations